Penerapan Business Intelligence dalam Dashboard Data Alumni Universitas Mulawarman - Mellyka, Ghalda; Islamiyah, Islamiyah; Widagdo, Putut Pamilih (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Mulawarman University's tracer study has not applied the business intelligence process and does not provide public access to alumni data. Therefore, it is necessary to design a dashboard to visualize alumni data with the application of business intelligence. Dashboards not only present information related to alumni but can also increase accessibility and support better decision-making in managing alumni data. The method used is the Business Intelligence Roadmap to visualize alumni data and measure the quality of graduates through six phases, namely justification, planning, business analysis, design, construction, and deployment. The results of system functionality testing show that the dashboard features function properly and meet the needs of the tracer study division, as evidenced through User Acceptance Testing (UAT).Keyword: Business Intelligence; Tracer Study; Alumni Quality; Dashboard; Data Visualization AbstrakTracer study Universitas Mulawarman belum menerapkan proses Business Intelligence dan tidak menyediakan akses publik terhadap data alumni. Oleh karena itu, diperlukan perancangan dashboard untuk memvisualisasikan data alumni dengan penerapan Business Intelligence. Dashboard tidak hanya menyajikan informasi terkait alumni, tetapi juga dapat meningkatkan aksesbilitas dan mendukung pengambilan keputusan yang lebih baik dalam pengelolaan data alumni. Metode yang digunakan adalah Business Intelligence Roadmap untuk memvisualisasikan data alumni dan mengukur kualitas lulusan melalui enam fase yaitu justifikasi, perencanaan, analisis bisnis, desain, konstruksi, dan penyebaran. Hasil pengujian fungsionalitas sistem menunjukkan bahwa fitur dashboard berfungsi dengan baik dan memenuhi kebutuhan divisi tracer study, sebagaimana dibuktikan melalui User Acceptance Testing (UAT).